Audit committee financial expertise and real earnings management - Ahmad Zaluki, Nurwati Ashikkin (2014)
The study examines the relationship between audit committee characteristics and real earnings management and test whether this constrains real earnings management activities.With the use of cross-sectional data of 100 companies rated by the Minority Shareholder Watchdog Group Malaysia as best in corporate governance practices in 2011, a multiple regression analysis is carried out.The study found that none of the variables of the audit committee characteristics could constrain real earnings management.The study adds to the existing literature on earnings management, particularly real earnings management.